Tourists Assessment of infrastructure Availability in GOA for Promoting Tourism: a Gap analysis - D'Mello, Carmelita; Subhash, Kizhakanveatil Bhaskaran Pillai (Anais Brasileiros de Estudos Turísticos, 2016)
The aim of this paper is to examine the perceptions of tourists visiting the state of Goa with regard to the importance given to and the satisfaction level with respect to the infrastructure, facilities, services and amenities available for tourism; to identify infrastructural strengths as well as problem areas which will enable various stake holders to take appropriate measures. 34 variables with respect to infrastructure, facilities, services and amenities were rated on importance given to and the satisfaction level through a structured questionnaire administered to 1000 tourists. Gap Analysis, which is based on Importance-Performance Analysis, was used to determine the gap between tourist perception of importance given before trip and satisfaction level after trip; and paired t-test was used to determine whether the gap was significant. Research findings reveal that in 30 out of 34 variables, there is a significant difference in tourist perception before and after the trip. Further, when plotted on an Importance-Performance Grid (Original 4 quadrant grid), 13 out of the 34 variables fall in Quadrant II (Concentrate here) indicating an urgent need to focus efforts and resources to improve the same, while the same, when plotted on the Modified 2 Quadrant Importance-Performance Grid, 15 variables fall in Quadrant II(High Priority)